PENGEMBANGAN BAHAN AJAR ENGLISH FUN LEARNING DENGAN APLIKASI CANVA MATERI HOW DO YOU GO TO SCHOOL KELAS IV MADRASAH IBTIDAIYAH - Suttrisno; Nasikah, Imroatun; Habibullah, M. Romadlon (Al-Mudarris: Journal Of Education, 2024)
The development of English Fun Learning teaching materials presents a creative approach to English language learning, incorporating engaging elements such as games, songs, instructional content, quizzes, and practice questions. This research aims to explore the development of teaching materials for English language instruction at MI Darul Falah Menilo in class IV, specifically focusing on the validation of the appropriateness of these materials concerning the topic "How do you go to school." The researchers employed a Research and Development (R&D) method, which is centered on creating and evaluating educational products. The study follows a structured process comprising seven stages: gathering initial information, planning, development, product trials, initial product revisions, field trials, and final product revisions. The teaching materials created are designed using the Canva application, tailored for English subjects in class IV. Validation results revealed that the teaching material design experts rated the materials at 91%, material experts also assessed them at 91%, and learning experts rated them at 93%. Additionally, student feedback on the learning materials achieved a response rate of 92%. Therefore, it can be concluded that the English Fun Learning teaching materials are highly suitable for use by students in their learning process.